A high-throughput SAMDI-mass spectrometry assay for isocitrate dehydrogenase 1. Issue 11 (16th April 2020) - Anderson, Sarah E.; Fahey, Natalie S.; Park, Jungsoo; O'Kane, Patrick T.; Mirkin, Chad A.; Mrksich, Milan
Abstract : This paper reports a SAMDI-mass spectrometry assay that can evaluate antagonists of cancer-associated isocitrate dehydrogenase 1 in high throughput. Abstract : The enzyme isocitrate dehydrogenase 1 (IDH1) catalyzes the conversion of isocitrate to alpha-ketoglutarate (αKG) and has emerged as an important therapeutic target for glioblastoma multiforme (GBM). Current methods for assaying IDH1 remain poorly suited for high-throughput screening of IDH1 antagonists. This paper describes a high-throughput and quantitative assay for IDH1 that is based on the self-assembled monolayers for matrix-assisted laser desorption/ionization-mass spectrometry (SAMDI-MS) method. The assay uses a self-assembled monolayer presenting a hydrazide group that covalently captures the αKG product of IDH1, where it can then be detected by MALDI-TOF mass spectrometry. Co-capture of an isotopically-labeled αKG internal standard allows the αKG concentration to be quantitated. The assay was used to analyze a series of standard αKG solutions and produced minimal error in measured αKG concentration values. The suitability of the assay for high-throughput analysis was evaluated in a 384-sample biochemical IDH1 screen. Cells expressing IDH1 were lysed and the lysate was applied to the monolayer to capture αKG, which was then quantitated using the SAMDI-MS assay. Cells in which IDH1 expression was reduced by small-interfering RNA exhibited a corresponding decrease in αKG concentration as measured by the assay. Application of the assay toward the high-throughput screening of IDH1 inhibitors or knockdown agents may facilitate the discovery of treatments for GBM.